Pengaruh Pijat Bayi Terhadap Penurunan Kadar Bilirubin - Desak Putu Kristian Purnamiasih; Pamenang, Ganjar Unggul (STIKES Ngesti Waluyo, 2023)
Hyperbilirubinemia is an increase in newborns bilirubin levels, especially in the first week of life. Hyperbilirubinemia is common in babies with birth weight < 2500 grams or babies born from mothers with a gestational age of less than 37 weeks. Treatment of hyperbilirubinemia uses several standard therapies, namely phototherapy, exchange transfusion, or a combination of phototherapy and exchange transfusion. Massage given to babies can improve digestive function through increasing nutrient intake and elimination which will directly help reduce the baby's serum bilirubin levels. The purpose of this study was to determine the effect of infant massage on bilirubin levels in infants with hyperbilirubinemia. The method used is a literature review obtained from 11 published articles including Google Scholar, PubMed, and Science Direct in the 2019-2021 period. The results from the literature review showed that massage on the whole body of the baby affects the motility of the gastrointestinal tract, increases blood circulation and lymph flow as well as enterohepatic circulation, and increases the amount of urine as a medium for excreting bilirubin. The comfort that babies get during the massage process greatly affects serotonin levels in babies and indirectly affects the function of the digestive tract. Improved digestive tract function will increase nutrient intake and elimination from the digestive and urinary tracts. Improved function of the digestive tract as evidenced by increased nutrient intake will help the process of conjugating bilirubin, while increasing defecation and elimination of urine will help remove conjugated bilirubin.